Spectrum of Colonic Polyps in a South Indian Urban Cohort - Jain, Mayank; Vij, Mukul; Srinivas, M.; Michael, Tom; Venkataraman, Jayanthi (Journal of Digestive Endoscopy, 2017)
Background: The histological nature of polyps by site prevalence and size is unclear. Aim: To determine the prevalence of polyps in patients undergoing routine lower gastrointestinal (LGI) endoscopy and identify the histological types and their characteristics by age, location and size. Materials and Methods: For this retrospective study, patients undergoing ileocolonoscopy or sigmoidoscopy between 2014 and 2016 were included. Data on age, gender, test indication, site and size of polyps and histology type were collected. Results: Two hundred and ninety (12.7%) of 2303 patients who underwent LGI endoscopy had colonic polyps (n= 317; single in 272 patients). The median age was 61.1 years (range 5-99 years) and 223 (76.4%) were men. Polyps were rare <40 years age (7.3%). By site, the polyp frequency in right colon was 6.9%, 3.9% in left colon and 4.6% in the rectum. Two thirds of polyps (64%) were <1cm size. The 3 common polyp types were adenomatous (48.9%), hyperplastic (23.7%), and inflammatory (22.4%). Adenomatous polyps were common above 60 years (p <0.0002), located often in right (35.5%) or left colon (42.6%), large in size (54.2%) and showed low grade dysplasia (89.7%). Hyperplastic polyps were most common in the middle aged and in the rectum (p <0.00001). Inflammatory polyps were the most common type below 40 years age. Almost all hyperplastic and inflammatory polyps were <1cm size (93.3% and 87.3%). Conclusions: Adenomatous polyps were the commonest type; especially >60 years age. High grade dysplasia and carcinoma were rare (10.3%). While two-thirds of polyps <1cm size were inflammatory or hyperplastic, 86% of large polyps were adenomatous.
Keywords: Adenomas; colon; colonoscopy; polyps